2020
DOI: 10.2147/ppa.s282147
|View full text |Cite
|
Sign up to set email alerts
|

<p>Assessing Knowledge and Perceptions of Alzheimer’s Disease Among Employees of a Pharmaceutical Company in Spain: A Comparison Between Caregivers and Non-Caregivers</p>

Abstract: Background: Raising knowledge about Alzheimer's disease (AD) may help in identifying the disorder, seeking earlier appropriate healthcare, and decreasing its stigma. The aim of this study was to determine the knowledge and perceptions towards people with AD among employees of a pharmaceutical company in Spain. Methods: A non-interventional, cross-sectional study was conducted among 447 employees. Participants answered demographic questions and completed the Alzheimer's Disease Knowledge Scale (ADKS). Caregiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Thus, we believe that public education about AD that takes cultural attitudes into account can increase public acceptance of people with AD [ 79 ], promote beliefs that dementia risk reduction is possible, and increase motivation for behavioral changes [ 80 ]. This, in turn, may hopefully lead to increased inclusion as well as better preventive behaviors among all citizens in the different ethnic groups, better identification of symptoms, and greater seeking of services [ 24 ]. Notably, interventions should go beyond information transmission and drawing attention to personal risk and prevention.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, we believe that public education about AD that takes cultural attitudes into account can increase public acceptance of people with AD [ 79 ], promote beliefs that dementia risk reduction is possible, and increase motivation for behavioral changes [ 80 ]. This, in turn, may hopefully lead to increased inclusion as well as better preventive behaviors among all citizens in the different ethnic groups, better identification of symptoms, and greater seeking of services [ 24 ]. Notably, interventions should go beyond information transmission and drawing attention to personal risk and prevention.…”
Section: Discussionmentioning
confidence: 99%
“…An examination of these ethnic differences is especially crucial in the case of AD, where aging and mental health compound to form negative stigma. An understanding of these ethnic differences may help to tailor culturally appropriate psychoeducational interventions and effective services for PwAD and their care givers [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although information about cognitive impairment has been widely disseminated through numerous awareness campaigns and educational programs, several studies have revealed different gaps in the public's knowledge regarding dementia and AD [3][4][5][6]. Adequate AD knowledge throughout society could lead to earlier identification of this disorder in the population, which would result in earlier appropriate healthcare for people with dementia and would decrease the stigma associated with AD [3].…”
Section: Introductionmentioning
confidence: 99%